Macroeconomic Effects of Oil Price Fluctuations on Emerging and Developed Economies. - Kacerovský, Tomáš; Maitah, Mansoor, 1962-; Malec, Karel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
This Diploma Thesis focuses on macroeconomic impacts of oil price fluctuation on emerging and developed economies. Primarily, it aims to challenge some widely accepted theoretical views regarding the impact of oil price fluctuations on world's economies. The initial chapter is devoted to the theoretical findings of institutions such as the International Monetary Fund and also to the claims of various economists such as Milton Friedman and Hyman Minsky. Emphasis is going to be put on the different effects of the 1970’ oil shocks on several economies including the United States and West Germany. The second chapter evaluates the most decisive events within the oil markets since the end of the Second World War such as the establishment of OPEC. The last two chapters are going to examine energy sectors of the Russian Federation and of the United States. Then a case study is to be driven outlining some different impacts of the 2014 energy crisis on these two economies.
Vedoucí práce: Mansoor Maitah
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses